2020
DOI: 10.1186/s13023-020-01441-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular basis of hepatocerebral mitochondrial DNA depletion syndrome in Japan: evaluation of outcomes after liver transplantation

Abstract: Background: Hepatocerebral mitochondrial DNA depletion syndrome (MTDPS) is a disease caused by defects in mitochondrial DNA maintenance and leads to liver failure and neurological complications during infancy. Liver transplantation (LT) remains controversial due to poor outcomes associated with extrahepatic symptoms. The purposes of this study were to clarify the current clinical and molecular features of hepatocerebral MTDPS and to evaluate the outcomes of LT in MTDPS patients in Japan. Results: We retrospect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 34 publications
(53 reference statements)
0
37
0
Order By: Relevance
“…Some patients with mutations in MPV17 have been treated with this strategy, but its efficacy is controversial because more than half of the transplanted children died in the post-transplantation period [ 159 ] ( accessed on 22 May 2021). A recent work has reported that liver transplant is only effective in patients with mutations in MPV17 with late onset and mild phenotype [ 160 ]. Liver transplantation has also been used in DGUOK patients since most of them show severe hepatic dysfunction.…”
Section: Targeted Therapies For Mddsmentioning
confidence: 99%
“…Some patients with mutations in MPV17 have been treated with this strategy, but its efficacy is controversial because more than half of the transplanted children died in the post-transplantation period [ 159 ] ( accessed on 22 May 2021). A recent work has reported that liver transplant is only effective in patients with mutations in MPV17 with late onset and mild phenotype [ 160 ]. Liver transplantation has also been used in DGUOK patients since most of them show severe hepatic dysfunction.…”
Section: Targeted Therapies For Mddsmentioning
confidence: 99%
“…p.Gln93Pro is the most common homozygous pathogenic variant found in multiple Arab families. 5 12 Nine out of 20 patients (45%) survived after LT. 5,12,14 On the other hand, a case with the same mutation as the present patient (p.Leu151fs and p.Pro98Leu) showed a good prognosis with survival for more than 20 years after LT, even though the patient experienced neurological deterioration. 12 Collectively, patients harboring p.Pro98Leu or p.Pro98Leu in at least one allele without marked neurological manifestations might have a better prognosis after LT. 12 The patient with mild neurological manifestations is being considered for a deceased donor LT owing to liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in deoxyguanosine kinase ( DGUOK ), mitochondrial inner membrane protein MPV17 , polymerase catalytic subunit ( POLG ), succinate-CoA ligase GDP/ADP-forming subunit alpha ( SUCLG1 ), twinkle MtDNA helicase ( TWNK ) and transcription factors A ( TFAM ) have been associated with hepatocerebral MDDS, with acute liver failure in infancy and hypoglycemia. DGUOK deficiency is one of the most frequent causes of hepatocerebral dysfunction ( 77 ). Recessive mutations of POLG , the main gene of mtDNA replication, are associated with a phenotype ranging from infantile hepatopathic poliodystrophy (Alpers-Huttenlocher syndrome) to sensory-ataxia neuropathy with dysarthria and ophthalmoplegia (SANDO), and spinocerebellar ataxia-epilepsy syndrome (SCAE) ( 78 , 79 ).…”
Section: Iem Presenting With Hypoglycemia In Childhoodmentioning
confidence: 99%